Mapping the landscape of urology: a new media-based cross-sectional analysis of public versus academic interest - Borgmann, Hendrik; Salem, Johannes; Baunacke, Martin; Boehm, Katharina; Groeben, Christer; Schmid, Marianne; Siegel, Fabian; Huber, Johannes (International journal of urology, 2018)
Objectives: To quantify public and academic interest in the urological field using a novel new media-based methodology. Methods: We systematically measured public and academic interest in 56 urological keywords and combined in nine subspecialties. Public interest was quantified as video views on YouTube. Academic interest was quantified as article citations using Microsoft Academic Search. The public-to-academic interest ratio was calculated for a comparison of subspecialties as well as for diseases and treatments. Results: For the selected 56 urological keywords, we found 226 617 591 video views on YouTube and 2 146 287 citations in the academic literature. The public-to-academic interest ratio was highest for the subspecialties robotic urology (ratio 6.3) and andrological urology (ratio 4.6). Prostate cancer was the central urological disease combining both a high public (20% of all video views) and academic interest (26% of all citations, ratio 0.8). Further diseases/treatments of high public interest were premature ejaculation (ratio 54.4), testicular cancer (ratio 11.4), erectile dysfunction (ratio 5.5) and kidney transplant (ratio 3.7). Urological treatments had a higher public-to-academic interest ratio (median ratio 0.25) than diseases (median ratio 0.05; P = 0.029). Conclusions: A quantification of academic and public interest in the urological field is feasible using a novel new media-based methodology. We found several mismatches in public versus academic interest in urological diseases and treatments, which has implications for research strategies, conference planning and patient information projects. Regular re-assessments of the public and academic interest landscape can contribute to detecting and proving trends in the field of urology.
Gesehen am 31.03.2020